Triggers For Stock Prices In Manufacturing Companies In The Food and Beverages Sector On The Indonesia Stock Exchange - Ni Nyoman Juli Nuryani (International Journal of Social Science and Business, 2021)
The global economy was sluggish due to the COVID-19 pandemic. Until March 2020, the economy began to decline, along with the pandemic outbreak throughout the world, including in Indonesia. People lost jobs due to the weakening of the national economy. This study aims to analyze the effect of Earning per Share (EPS) Net Profit Margin (NPM), Gross Profit Margin (GPM) Total Assets Turnover (TATO), and Total Assets Turnover (TATO) on company stock prices in manufacturing in the food and beverage sector. It was listed on the Indonesia Stock Exchange (IDX) with an observation period of 2016-2021. The population and sample in this study are the quarterly financial reports of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange. The sampling method used is the purposive sampling method, with a total sample of 252 quarterly financial statements taken from 12 companies. The data used in this research is secondary data. Furthermore, the data collected was tested by multiple linear regression analysis, processed using the SPSS version 18 application. The results showed that partially EPS and NPM had a positive and significant effect on stock prices, while GPM had no significant effect on stock prices, and TATO had a negative effect. And significant to stock prices. Simultaneously, EPS, NPM, GPM, and TATO have a positive and significant effect on stock prices with a coefficient of determination of 67.4%.